PENATALAKSANAAN FISIOTERAPI PADA KASUS SINDROM OBSTRUKSI PASCA TUBERKULOSIS PARU : STUDI KASUS - Lini Dewi Mahesti; Tiara Fatmarizka; Prayitno (Jurnal Cakrawala Ilmiah, 2023)
Introduction : Tuberculosis is a pathological condition caused by the bacterium Mycobacterium tuberculosis. Even though it has been treated, sometimes pulmonary TB cases still leave sequelae called TB sequelae. Improper management of TB sequelae can increase the risk of mortality. Thus, it is necessary to have a structured rehabilitation program in cases of TB sequelae. Purpose : to determine the effect of physical therapy exercise on the management of TB sequelae cases. Methods : Research method using a case report. Outcome measurement: measurement of sputum using auscultation, muscle spasm using palpation, examination of lung volume capacity using Voldyne and peak flow meter, examination of thoracic cage expansion using the midline. Results: after 5 times of therapy, there was decreasing sputum volume, decreasing spasm of the accessory muscles of breathing, improve thoracic expansion, and improve lung volume capacity. Conclusions: Administration of programmed exercise in cases of TB sequelae can increase lung volume and increase thoracic expansion.